Culture, Spaces, and People Urban Dynamics in Contemporary India - Jain, Daksh (Urban futures, 2023)
This volume discusses the nuances of cultural phenomena in the transforming urban landscape of Indian cities. It focuses on the role of globalization, transitioning economic patterns, National Urban policies in changing their urban landscape. The volume argues how culture is an important determinant of the emergent urban patterns. It decodes and determines the human centered inter-linkages such as social, cultural, economic, and political and their reactions in the transformations in urban morphology to understand the spatial perspective and visualization of new emerging cultural phenomena. The book reflects on the contemporary global forces and currently operational national urban policies that have enforced new dynamics of consumption, lifestyles, and institutions. Further, it also examines the ways in which these forces come together to create new hybrid cultures which manifest in spatial practices. With detailed case studies of different cities, this book will be of interest to students, teachers, and researchers of urban planning, cultural studies, urban sociology, urban geography, history, urban design, urban conservation, and policy studies. It will also be useful for professionals working in the field of smart cities in India and abroad, planning authorities, urban scientists, cultural tourists, artists, local cultural enthusiasts, and those interested in studying the urban conditions of Indian cities.